Waqf as a tool for rendering social welfare services in the social entrepreneurship context - Alam, Md Mahmudul; Shahriar, Shawon Muhammad; Said, Jamaliah; E Elahi, Mohammad Monzur (Universiti Sultan Azlan Shah, MALAYSIA (USAS), 2018)
The concept of Islamic entrepreneurship centers on ensuring community well-being as the priority, which is one of the important objectives (Maqasid) of the Islamic Shari'ah.Historically, waqf played a significant role in the Islamic economic system, particularly in rendering exemplary welfare services in the areas of healthcare, education, social welfare, environmental, and other community-based programs.However, only a few success stories in recent history have institutionally utilized the properties of waqf under proper management to achieve its substantial objectives. This study uses the literature review as basis to analyze the reasons behind the successful utilization of waqf as an effective tool to ensure social welfare services in the past, as well as how this model can be replicated by considering current contexts. This study will assist Islamic valuecentric entrepreneurs, regulatory authorities, investors, and researchers to gain an overall insight into the potentials of waqf as a tool for rendering commendable social welfare services.